(untitled) - Foster, Nigel G. (London, 1993)
This is a reference source for the professions and others who wish to obtain fundamental information about the German legal system and German law. It also serves as a text for undergraduate and postgraduate students who study the German legal system as a part of a university, polytechnic or college course. Whilst it is tailored for those studying the German legal system as a part of a law and German degree, it may also be of interest to those on multidisciplinary European studies degree courses- politics, history, economics and business studies courses which have included the study of aspects of German law and legal system. The chapters on historical legal development, constitutional law, sources of law, the legislative process, legal professions, court structure, legal education, legal aid and the administration and implementation of justice are particularly relevant. Part two concentrates on substantive law in detail and covers the principal areas of public and civil law in Germany. The text includes a full table of legislation and cases cited in the text, and extracts from the Grundgesetz. Nigel Forster is a member of the British-German Jurists Association and author of "Blackstone's EEC Legislation".
Keywords: Law; Luật; Germany,Nước Đức